ANALISIS DAMPAK DAN EFEKTIVITAS ADANYA UNDANG UNDANG NO 11 TAHUN 2020 TENTANG CIPTA KERJA PERPAJAKAN TERHADAP PERHITUNGAN PENGKREDITAN PAJAK MASUKAN PADA PT SUPRAJAYA DUARIBU SATU - Sofyan Hadi; Jennifer (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
This study was conducted to determine whether there is an impact and effectiveness of the taxation work copyright law in calculating input tax credits at PT Suprajaya Duaribu Satu. This research is important so that PT Suprajaya Duaribu Satu can understand and analyze the work copyright law no. 11 of 2020 on input tax crediting. This type of research is a case study. This study uses a qualitative method with a descriptive approach. Data collection techniques using documentation studies. Based on the results of the documentation, this research shows that the crediting of input taxes at PT Suprajaya Duaribu Satu since the existence of the work copyright law no 11 of 2020 has had an impact. One of them is about crediting input tax wherein the Input Tax that is not reported in the Periodic VAT SPT that is notified and/or found at the time of inspection can be credited. One point that has no impact is about entrepreneurs who can credit input taxes before being confirmed as PKP, although not all points of change that exist in the work copyright law no 11 of 2020 have an impact, but with the work copyright law this results in a tax credit the input to PT Suprajaya Dua Thousand One has changed so that it becomes more effective.